Bioethical Issues and Secondary Prevention for Nonoffending Individuals with Pedophilia - Heasman, Ainslie (Cambridge quarterly of healthcare ethics, 2019)
Child sexual abuse is a global problem with significant emotional, psychological, and financial implications to victims, perpetrators, and society. Most child sexual abuse prevention programs target young children or those who have already engaged in abusive behavior, in order to prevent further offending. There are numerous secondary prevention programs targeting individuals at-risk of various health conditions in an effort to reduce the likelihood they will go on to experience a particular illness or disease. Considerable research exists regarding the risk factors for engaging in child sexual abuse and more specifically the factors contributing to reoffense. We argue that engaging in secondary prevention programs for people with pedophilia, in order to prevent child sexual abuse, is an ethically responsible and necessary practice. Secondary prevention programs with this focus are reviewed, along with the implications of mandatory reporting in doing this work.